The Influence of Injection Timing on Performance Characteristics of Diesel Engine Using Jatropha Biodiesel with and without Partial Hydrogenation - Fajar, Rizqon; Setiapraja, Hari (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2014)
Experimental research has been conducted to investigate the effects of blend of hydrogenated and unhydrogenated Jatropha biodiesel with diesel fuel in volume ratio of 30:70 (B30) on combustion characteristics (BSFC, thermal efficiency and smoke emission) of single cylinder diesel engine. In this experiment, engine speed was kept constant at 1,500, 2,500, and 3,500 rpm with maximum engine load at BMEP 5 bar and injection timings were varied. Experimental result showed that at engine speed 1,500 rpm, BSFC of B30 hydrogenated and unhydrogenated Jatropha biodiesel were higher than it of diesel fuel at all injection timings (10° to 18° BTDC). At the same condition, partial hydrogenated Jatropha biodiesel showed higher BSFC than unhydrogenated Jatropha biodiesel. However, the difference in BSFC became smaller for all fuels at engine speed 2,500 rpm and 3,500 rpm at all injection timing. Jatropha biodiesel with and without partial hydrogenation tend to have higher thermal efficiency compared with diesel fuel at all engine speed and injection timing. The best injection timings to operate B30 Jatropha biodiesel with and without hydrogenation were 14°, 18° and 24° BTDC at engine speed 1,500, 2,500, and 3,500 rpm respectively. This conclusion was deduced based on the minimum value of BSFC and the maximum value of thermal efficiency. Smoke emissions for all fuels were in the same level for all conditions.